Processions (Washington, D.C.)
viii, 263 sayfa
Keywords: “Processions of all kinds-military, civic, religious, and more-were hallmarks of the ancient and medieval world. Yet urban processions in Byzantine culture have never been thoroughly studied, even though there were as many as two processions a week in Constantinople alone, often featuring eminent individuals like the emperor and the patriarch (and less prominent people, like the teams who decorated the streets). In an introduction and ten chapters, this volume examines a millennium of medieval processions through analysis of texts, artifacts, and images. Byzantium did not, of course, exist in a vacuum. Byzantine processions are here set alongside those occurring at the borders of the Byzantine world: the Latin West, the Islamic East, and, of course, Jerusalem, the center of the Mediterranean's sacred world. This comparative approach lets us better see how the Byzantines operated in a complex global network defined by local contexts, how the Byzantines positioned themselves within this network, and the nature of the Byzantine legacy to their Islamic, Catholic, and Orthodox inheritors“ --